Language situation and language policy in-education in Zimbabwe: A perspective towards Tonga learners - Hang’ombe, Khama; Mumpande, Isaac (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
This study examines the language situation in Zimbabwe with a bias towards the language policy in-education. It seeks to establish the effect of the language policy in-education in Zimbabwe on the academic performance of the Tonga learners. The researchers sought to establish how the use of either Shona or Ndebele as medium of instruction and the learning of these languages as subjects negatively impacted on the performance of Tonga learners in primary schools. Our analysis goes beyond understanding the academic performance of Tonga learners and also seeks to establish the impact of such a status quo on other aspects of the Tonga people’s lives such as culture and identity because whatever goes on in the classroom has a bearing on these social arenas. The data for this study were collected from native Tonga speakers, especially those that went to school before the language policy changed, that is, who were using Shona, Ndebele and/or English as medium of instruction in the education system in Zimbabwe at lower grades. The study established that the peripheralisation and marginalisation of Tonga in the education sector dealt a huge blow on the psyche, and self-confidence of the Tonga learners and their society at large in Zimbabwe. The study concluded that there is however, hope for the Tonga learners and community, ensuing from the official recognition of Tonga language, among other former marginalised languages, in the 2013 National Constitution and the subsequent amendment of the Education Act in 2020. These two critical developments will, without doubt, reverse the hegemony of Shona and Ndebele languages as medium of instructions in schools.